2021
DOI: 10.1200/jco.20.01802
|View full text |Cite
|
Sign up to set email alerts
|

CanDirect: Effectiveness of a Telephone-Supported Depression Self-Care Intervention for Cancer Survivors

Abstract: PURPOSE Depression in post-treatment cancer survivors is common and can impair quality of life. CanDirect is a novel, telephone-delivered depression self-care intervention for cancer survivors. We conducted a randomized controlled superiority trial to compare CanDirect with usual care (UC) in this population. METHODS Participants completing cancer treatment within the past 10 years who had mild-moderate depressive symptoms with or without major depression were recruited from clinical and community settings in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 80 publications
0
42
0
Order By: Relevance
“…Coaching was delivered in short telephone calls, using standardized protocols. The results of this research indicated beneficial effects of the coached interventions in different target populations on depression at 6 months: adjusted effect sizes were 0.42 (95% CI 0.08, 0.77) for a coached vs self-guided intervention among patients with chronic physical conditions not receiving therapy at study entry [9], and 0.60 (95% CI 0.33, 0.87) for a coached intervention vs usual care among cancer survivors [10]. These effect sizes are consistent with those reported in meta-analyses [5,6,11].…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Coaching was delivered in short telephone calls, using standardized protocols. The results of this research indicated beneficial effects of the coached interventions in different target populations on depression at 6 months: adjusted effect sizes were 0.42 (95% CI 0.08, 0.77) for a coached vs self-guided intervention among patients with chronic physical conditions not receiving therapy at study entry [9], and 0.60 (95% CI 0.33, 0.87) for a coached intervention vs usual care among cancer survivors [10]. These effect sizes are consistent with those reported in meta-analyses [5,6,11].…”
Section: Introductionmentioning
confidence: 82%
“…Despite the evidence of effectiveness of the intervention among cancer survivors [10], the lack of associations between adherence and outcomes in the cancer survivor cohort is perplexing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations